Polyimide film with low thermal expansion and high transparency by self-enhancement of polyimide/SiC nanofibers net. Issue 34 (23rd May 2018) - Liu, Feiyan; Liu, Zhihong; Gao, Shuyu; You, Qingliang; Zou, Liyong; Chen, Jia; Liu, Jiyan; Liu, Xueqing
Abstract : Polyimide films with low thermal expansion and high transparency were fabricated by homogeneity enhancement of nanofibers net. The nanofibers net that composed of polyimide and SiC nanoparticles is obtained by electrospinning technic. Abstract : A facile approach to synthesize a polyimide (PI) film with enhanced dimensional stability, a high mechanical property and optical transparency is presented by embedding the partial imidized PI/SiC nanofiber-net in a poly(amic acid) (PAA) solution, followed by removing the solvent and imidization of the PAA. The nanofiber-network self-filled PI film demonstrates a much lower thermal expansion coefficient (CTE), an excellent mechanical property and high transparency retention in comparison to the film fabricated by solution cast. When the SiC content is 6 wt% in PI/SiC nanofibers, the CTE values for the PI film containing 25 wt% PI/SiC nanofibers are 2.80 times lower than the solution cast PI/SiC film. The tensile strength and modulus for the PI/SiC fiber filled film are also improved by 159% and 91% respectively in comparison to the solution cast SiC/PI film. In addition, the PI/SiC nanofiber-network filled PI film exhibits a high optic transparency. The significant improvement in aforementioned properties is contributed to by the long and continuous nanonetwork which acts as a frame to maintain the stable dimension and endow the film with high mechanical properties. Moreover, the nanosized SiC particles were constricted within the nano-fiber to avoid light scattering, so the high transparency of the film was retained.